2013
DOI: 10.1021/am403943q
|View full text |Cite
|
Sign up to set email alerts
|

Strong Improvements of Localized Surface Plasmon Resonance Sensitivity by Using Au/Ag Bimetallic Nanostructures Modified with Polydopamine Films

Abstract: In the present work, the standard monometallic localized surface plasmon resonance (LSPR) biosensing sensitivity is highly improved when using a new system based on glass substrates modified with high-temperature annealed gold/silver bimetallic nanoparticles (Au/Ag bimetallic NPs) coated with polydopamine films before biomolecule specific immobilization. Thus, different zones of bimetallic NPs are spatially created onto a glass support thanks to a commercial transmission electron microscopy (TEM) grid marker i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 59 publications
1
44
0
Order By: Relevance
“…5C. It was found that plasmon absorption shifts linearly to longer wavelength with increasing the refractive index 22, 47, 48 . In addition, only absorption is considered here and the influence of scattering are neglected due to higher absorption than scattering of nanorods 49 .…”
Section: Resultsmentioning
confidence: 97%
“…5C. It was found that plasmon absorption shifts linearly to longer wavelength with increasing the refractive index 22, 47, 48 . In addition, only absorption is considered here and the influence of scattering are neglected due to higher absorption than scattering of nanorods 49 .…”
Section: Resultsmentioning
confidence: 97%
“…9,10 In addition, owing to the structure and element dependent localized surface plasmon resonance (LSPR), the BMNPs can be applied in various optoelectronic devices to improve the optical output, conversion efficiency and detection sensitivity. [11][12][13][14][15] At the same time, the monometallic Ag and Pd NPs individually have been important materials in optical, plasmonic and catalytic applications. 16,17 At this stage, the idea of combining both Ag and Pd atoms in a single nanostructure can further extend their applicability and thus the fabrication of bimetallic Ag x Pd 1Àx nanostructures by controlling their morphology and elemental composition can be promising approach to explore the functionality and usability for the related and novel applications.…”
Section: Introductionmentioning
confidence: 99%
“…Both theoretical and experimental results in the literature have shown that SPR peak position depends on particle diameter, aspect ratio, shape, surface coating, surfactants, surface morphology, volume, coating of other nanoparticles, and aggregates of gold substrates. [45][46][47][48][49][50][51][52][53][54] Sigmoidal responses were observed as a function of the coverage of proteins (in log scale) on gold particles deposited on flat substrates. 55 This is similar to the Langmuir-Freundlich isotherm curve, 47 which is not an intrinsic response of silver layer on gold substrate.…”
Section: Resultsmentioning
confidence: 99%